Femtojoule-Power-Consuming Synaptic Memtransistor Based on Mott Transition of Multiphasic Vanadium Oxides - Iqbal, Shahid; Duy, Le Thai; Kang, Hyunwoo; Singh, Ranveer; Kumar, Mohit; Park, Jucheol; Seo, Hyungtak (Advanced Functional Materials, 2021)
To realize the potential of Mott transition of multiphasic vanadium oxides (VOx) for memory applications, the development of VOx memtransistors on SiO2 wafer is introduced. Through electrical characterizations, the volatile memory behaviors of the VOx memtransistors are observed in both two- and three-terminal measurements. Their capacitive memory and resistive switching mechanisms are strongly related to the mixed VOx/SiO2 interface (called VSiOx). VSiOx supports the Mott transition in VOx at low bias voltages (<0.5 V), leading to the low power consumption of the memtransistor. Moreover, the fast switching time (≈35 ns) and tunable memory retention with the synaptic functions (potentiation and depression) of the memtransistors (by using the gate and drain biases) are demonstrated. Overall, the findings open up major opportunities for constructing ultrafast and femto-joule power-consuming neuromorphic devices.
Keywords: Electrical characterization; Low bias voltage; Low-power consumption; Memory applications; Memory retention; Mott transitions; Resistive switching mechanisms; Terminal measurements; fast switching; interfacial Mott VSiO x channel; memtransistor devices; Mott transition; synaptic functions; volatile thin film transistors